Long-term antibiotic resistance surveillance of gram-negative pathogens suggests that temporal trends can be used as a resistance warning system - Sorberg, Mikael (2002)
Antibiotic resistance among Gram-negative bacteria and antibiotic consumption were investigated at the Karolinska Hospital, Stockholm, Sweden over a 12-y period. The investigation showed an increase in ciprofloxacin resistance of Escherichia coli from 0% in 1991 to 7% in 1997 and to 11% in 1999. Resistance among Pseudomonas aeruginosa isolates to ciprofloxacin increased from 2.5% in 1991 to 9.0% in 1997 and to 13% in 1999. Resistance levels for norfloxacin showed the same high statistical significance in terms of the temporal trend. A more detailed analysis showed higher resistance against norfloxacin in specific wards. Relationships between antibiotic use and antibiotic susceptibility showed different patterns. The increased ciprofloxacin resistance of E. coli and P. aeruginosa during the study period was paralleled by an increased consumption of quinolones. During the 12-y study period the total use of cephalosporins increased 2.5-fold, while the levels of E. coli resistance to cefuroxime and cefotaxime remained stable. A third pattern was seen with trimethoprim-sulfamethoxazole, namely increasing resistance of E. coli as the use of trimethoprim-sulfamethoxazole declined. The analysis of resistance levels and antibiotic consumption in the present study suggests different mechanisms for the increased resistance. The significant trend of increased resistance to antibiotics over time constitutes an important warning system.